Patient Safety Risks during On-Demand Telehealth Referrals and Implications for Human Factors Research. (September 2021) - Gomes, Kylie M.; Adams, Katharine T.; Booker, Ethan; Ratwani, Raj M.
The COVID-19 pandemic has rapidly accelerated the adoptionof on-demand telehealth as a way to keep patients and providers safe from viral transmission. However, theconstrained timelines and challenging conditions under which telehealth was implemented along with the factthat many patientsand providers are interacting in a new modality raisesconcerns about the potential for unintended patient safety risks that have yet to be fully understood. With the surge in telehealth patient volumeduringthe pandemic, on demand telehealth has served as a way to triageand refer patients who need additional in-person evaluation and treatment. One safety concern is whether patients who are referred are successfully following through on in-person care referrals as thefailure to seekin-person care may lead to increased risk of delayed or missed diagnosis. This study aimsto evaluate whether patientsare successfully fulfilling their in -person referralsfollowingareferralfromon-demandtelehealth through retrospective analysis of a subset of telehealth referral datafrom a large healthcare system. Of the 911 on-demand telehealth visitswith a referral to in-person care, only 689showed anin-person care encounter following the telehealthvisit and only 75-85% ofmore immediate urgency in-person referrals were fulfilled within the recommended time period of 24 hours. This preliminary data highlights theneed for amore comprehensiveanalysisof the telehealth referral processand the application of human factors methodsto understand and address barriers and risks associated with telehealth referrals and successful follow up.